Research priorities in 2012 for the effective management of childhood obesity. Issue 1 (22nd April 2013) - Taylor, R. W.; Robinson, A.; Espinel, P. T.; Baur, L. A.; Wake, M.; Sabin, M. A.
Summary In 2010, the Management Stream of the Australasian Child and Adolescent Obesity Research Network (ACAORN) undertook a Delphi survey asking 'What research questions remain to be addressed in the effective management of child and adolescent obesity?' Members of ACAORN, the Child and Adolescent Obesity Clinics of Australasia Network (CAOCOA‐Net) and attendees at the Child Obesity symposium at the annual scientific meeting for the Australian and New Zealand Obesity Society (ANZOS) contributed to three rounds of survey development. Although reasonable concordance in ratings was evident for all 10 questions, 'determining the best strategies for long‐term weight management' and 'how best to support the primary healthcare system to achieve these strategies' were clearly identified as the highest research priorities. Other priorities included 'how best to identify the right children with whom to intervene' and 'managing factors which impact on service delivery'. Identifying priority research areas from those working in the field offers the opportunity to stimulate research collaboration and provide justification for funding applications.